Periodic and boundary value problems for second order differential inclusions. (2001) - Palmucci, Michela; Papalini, Francesca
Abstract : In this paper we study differential inclusions with boundary conditions in which the vector field F ( t, x, y ) is a multifunction with Caratheodory type conditions. We consider, first, the case which F has values in ℝ and we establish the existence of extremal solutions in the order interval determined by the lower and the upper solution. Then we prove the existence of solutions for a Dirichlet problem in the case in which F takes their values in a Hilbert space.